2019
DOI: 10.1021/acs.langmuir.9b00670
|View full text |Cite
|
Sign up to set email alerts
|

Facile Dissolution of Zein Using a Common Solvent Dimethyl Sulfoxide

Abstract: The conformation and stability of zein in solution are closely associated with its solvation process and influence the mechanical properties of the related zein-based materials. In this work, a common solvent dimethyl sulfoxide (DMSO) was used to dissolve zein, rather than solvents frequently used such as aqueous ethanol and acetic acid. It was found that DMSO could dissolve zein readily and the solution was stable for at least 2 weeks. Rheological analysis and small-angle X-ray scattering (SAXS) were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…To further analyze the changes in the crystalline shape of each PRX elastomer, SAXS measurements were performed. As shown in Figure S2a–e, the shape of the crystalline structure was analyzed based on the pair-distance distribution function [ P ( r )], which was obtained from the SAXS raw data (Figure S4) by using the GNOM program. , It is known that the P ( r ) distribution is reflective of the shape of the nanocrystalline structures while the peak intensity of P ( r ) is proportional to the number of such structures present . Generally, the peaks in the P ( r ) curve represent the distance from the point of origin ( r = 0 nm) of the scattered electron pair in the crystalline structure to the boundary point ( r = x nm) in the same crystalline area .…”
mentioning
confidence: 99%
“…To further analyze the changes in the crystalline shape of each PRX elastomer, SAXS measurements were performed. As shown in Figure S2a–e, the shape of the crystalline structure was analyzed based on the pair-distance distribution function [ P ( r )], which was obtained from the SAXS raw data (Figure S4) by using the GNOM program. , It is known that the P ( r ) distribution is reflective of the shape of the nanocrystalline structures while the peak intensity of P ( r ) is proportional to the number of such structures present . Generally, the peaks in the P ( r ) curve represent the distance from the point of origin ( r = 0 nm) of the scattered electron pair in the crystalline structure to the boundary point ( r = x nm) in the same crystalline area .…”
mentioning
confidence: 99%
“…As expected, the FTIR spectrum of zein/SDS film showed characteristic peaks corresponding to amide I, amide II, and amide III at 1652, 1534, and 1245 cm −1 , respectively. 66,67 The peak at 1214 cm −1 was due to SO stretching vibrations of SDS. 68 In comparison to zein/SDS film, the spectrum of Fe(III)@zein/ SDS adhesive showed that this peak was shifted to 1172 cm −1 , suggesting chelation between Fe(III) ions and sulfonic acid groups in SDS, which were intercalated in the zein molecular chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, formulation ZIFI 3, fabricated using the highest zein concentration (30% w/v), possessed an N value of 1.321, indicating the shear-thinning behavior of the system. The difference in the obtained flow behaviors indicates the dependence of viscosity on the concentration of the used polymer [55]. In simple words, this can be attributed to the increased extent of entanglements between the polymer chains at high concentrations.…”
Section: Rheological Propertiesmentioning
confidence: 95%